(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2015)
It is an established fact that life-style related behavioral factors are mainly responsible for cardiovascular diseases. Doctors are playing very important role in imparting knowledge to the society as to how to stay away from diseases by adopting preventive measures. We studied the prevalence of life-style related risk behavior in medical students and to determine the effect of these factors on blood pressure. The study was conducted on 249 medical students, from which 182 were boys and 67 were girls of age group 16-29 years. In a random cross-sectional survey of medical students were interviewed for anthropometric measurements, BMI, dietary habits, physical activity and cardiovascular parameters. Cardiovascular risk factors in boys of medical college are more than girls. Out of 182 boys studied 48 [26.37%] were having their blood pressure values higher than 130/90 mm Hg. because of their faulty living/eating habits. Junk food, cola, alcohol and smoking is on rising trend with predominance of physical inactivity and overweight and as a consequence rise in the blood pressure. Dietary and exercise counseling is required for such students. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22675 Bangladesh J Physiol Pharmacol 2014; 30(2):1-8